Cobalt-Magnesium and Iron-Magnesium Complexes with Weakened Dinitrogen Bridges - Dugan, Thomas R. (2013)
The cooperative binding of N(2) by late transition metals and main-group metals is a promising strategy for N-N bond weakening and activation. We report the use of activated Rieke magnesium for reduction of iron and cobalt complexes supported by bulky β-diketiminate ligands. Binding of N(2) is accompanied by assembly of a linear M-NN-Mg-NN-M (M = Co, Fe) core with N-N bonds that are weakened, as judged by infrared spectroscopy. Both the cobalt and iron complexes require THF solvent, because of Mg-THF binding. The cobalt complex can be isolated as a pure solid, but the iron complex is stable only in solution. These results demonstrate the correlation between the binding mode and N-N weakening in heterobimetallic N(2) complexes.